On the curved wedge condition and the continuity moduli of conformal mappings - Bely, V. I.; Pritsker, I. E. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A Jordan curve L is studied, which satisfies an interior or exterior wedge condition for wedges of various geometric forms. We obtain estimates of the continuity moduli for the conformal mappings of the exterior (interior) of L onto the exterior (interior) of the unit disk.